2017
DOI: 10.1259/bjr.20170344
|View full text |Cite
|
Sign up to set email alerts
|

Fat fraction mapping using magnetic resonance imaging: insight into pathophysiology

Abstract: Adipose cells have traditionally been viewed as a simple, passive energy storage depot for triglycerides. However, in recent years it has become clear that adipose cells are highly physiologically active and have a multitude of endocrine, metabolic, haematological and immune functions. Changes in the number or size of adipose cells may be directly implicated in disease (e.g. in the metabolic syndrome), but may also be linked to other pathological processes such as inflammation, malignant infiltration or infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 130 publications
1
63
0
2
Order By: Relevance
“…Additionally, Bland–Altman plots showed good agreement of PFF measurements between the two interobservers in the present study. Our results are consistent with Bray et al, who show that fat fraction (FF, the proportion of the acquired signal derived from fat protons) has become established as a clinical and research tool …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, Bland–Altman plots showed good agreement of PFF measurements between the two interobservers in the present study. Our results are consistent with Bray et al, who show that fat fraction (FF, the proportion of the acquired signal derived from fat protons) has become established as a clinical and research tool …”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with Bray et al, who show that fat fraction (FF, the proportion of the acquired signal derived from fat protons) has become established as a clinical and research tool. 29 Our study shows that there is a strong positive correlation between PFF and HFF; visceral abdominal adipose tissue is the main determinant of both liver and pancreas fat content in T2DM subjects and that liver and pancreas fat content are positively related with feeding time and fasting blood-glucose levels. Rossi et al reported similar results after observations of obese population.…”
Section: Discussionmentioning
confidence: 48%
“…MR signal arises from protons within different chemical environments (ie, water and fat molecules from body), giving rise to small differences in their resonance frequencies, thereby allowing for quantification. Several MR approaches used to quantify pancreatic fat pancreas include the following techniques. Magnetic resonance spectroscopy (MRS): The noninvasive test that is considered the gold standard to quantify pancreatic fat is MRS. MRS testing requires the user to manually position a voxel to contain as much pancreatic tissue as possible (avoiding blood vessels and the main pancreatic duct) . MRS acquired using point‐resolved spectroscopy or stimulated echo acquisition mode sequences is used to derive a spectrum of the constituent proton signals. Chemical‐shift MRI (CSI): CSI involves acquisition of imaging signal to match the chemical shift between the main fat and water peaks.…”
Section: Computed Tomography and Magnetic Resonance Imagingmentioning
confidence: 99%
“…Generated “in‐phase” and “out‐of‐phase” images can then be subtracted to estimate fat content . Errors from background magnetic‐field inhomogeneity may limit quantifying‐tissue fat content, as do difficulties with the quantification of very high/low fat fraction measurements . Qualitative fat assessment is also feasible with CSI. Proton density fat fraction (PDFF) mapping: PDFF mapping addresses limitations of multipoint Dixon quantification, many of which are specifically relevant to pancreatic imaging.…”
Section: Computed Tomography and Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation